Upper Secondary School Student Digital Information Fluency: A Second-Order Confirmatory Factor Analysis - Sarannisa Muangchan; Aukkapong Sukkamart; Paitoon Pimdee; Jaruwan Ployduangrat; Akkarin Thongkaw (My University, 2024)
This research aimed to investigate the components of digital information fluency (DIF) skills among high school students. The sample comprised 354 teachers from schools supervised by the Office of the Basic Education Commission (OBEC) Secondary Educational Service Area Offices (SEAOs), selected through multiple-stage random sampling. Their opinions concerning student DIF skills were collected via a questionnaire and analyzed using descriptive statistics and a 2nd -order confirmatory factor analysis (CFA). Results revealed a high overall level of opinion among technology teachers regarding student DIF skills, with Digital Data Communication (DDC) exhibiting the highest weight (β = 1.00, R2 = 1.00), followed by Digital Literacy (DL) (β = 0.97, R2 = 0.95), and Digital Information Management (DIM) (β = 0.91, R2 = 0.83). This study contributes to the literature by providing insights into the perception of DIF skills among teachers, shedding light on areas of emphasis in digital fluency education. Additionally, it offers valuable implications for curriculum development and teacher training programs aimed at enhancing students' digital literacy in today's information-rich environment.
Keywords: Factor (programming language); Gender and Technology in Education